4.7k views
4 votes
2y=12+4y please show work

2 Answers

1 vote
Ok so you have to take away the y term with that is added with the non term and subtract it with the other y term since they’re both positive. Once you get your answer, divide it with the no term number and there’s your final answer.

2y=12+4y
-4y -4y

6y=12

12/6=2

Answer is 2
User Insectatorious
by
5.4k points
3 votes

Answer:Step 1: Simplify both sides of the equation.

2y=4y+12

Step 2: Subtract 4y from both sides.

2y−4y=4y+12−4y

−2y=12

Step 3: Divide both sides by -2.

−2y

−2

=

12

−2

y=−6

Answer:

y=−6

Explanation:

User Christian Owens
by
5.6k points